Phytopharmaceutical Diversity of Baka People in the Southern Cameroon - Afiong, Natacha Nana; Fils, Pascal Billong; Betti, Jean Lagarde; Muhesi, Eloge Kambale; Brull, Guillermo Ros; Julia E. FA; Funk, Stephan Michael (CV. Literasi Indonesia, 2024)
Medicinal plants take a fundamental place in people's livelihoods. They seem to be a palliative therapeutic option for health problems. The knowledge of traditional uses of plants for healing held by indigenous people is an asset to the valorization of traditional medicine, which is increasingly solicited for the treatment of many diseases. The aim of this research is to improve know-how on plant species employed in the traditional pharmacopoeia practiced by the Baka people, recognized as great healers. Data were collected between 2018 and 2019 from 75 households distributed in five villages in the Mintom subdivision, Southern Region of Cameroon. The so-called popular ethnobotanical survey method was used. One thousand six hundred and thirty-five (1 635) citations and six hundred and five (605) recipes were recorded, involving 210 plant species, distributed in 183 genera and 75 families. A total of 69 health problems were identified and distinguished in 13 groups of diseases. Results reveal that for the same diseases, each village uses its own list of plants. The study area is highly diverse in terms both flora and uses. This paper can therefore be seen as a continuation of the research and development of plants-based medicines. It is also in the line with the import-substitution policy for valorization of Cameroonian.